2015
DOI: 10.3389/fpsyg.2015.00273
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers and applications of attachment theory

Abstract: Editoriale dell'E-Book internazionale di cui l'autrice è Topic Editor, introduce e commenta lo stato dell'arte sull'attaccament

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To conclude, our findings are consistent with attachment theory and the related literature. They confirm the importance of using implicit dimensions of attachment, as well as global attachment classifications, to better understand an adult’s psychological functioning ( Salcuni, 2015 ), and better define their parenting profile ( De Palo et al, 2014 ), particularly when considering such complex psychological traits as parenting self-esteem.…”
Section: Discussionmentioning
confidence: 58%
“…To conclude, our findings are consistent with attachment theory and the related literature. They confirm the importance of using implicit dimensions of attachment, as well as global attachment classifications, to better understand an adult’s psychological functioning ( Salcuni, 2015 ), and better define their parenting profile ( De Palo et al, 2014 ), particularly when considering such complex psychological traits as parenting self-esteem.…”
Section: Discussionmentioning
confidence: 58%
“…The findings in Experiment 2 showed that a fearful attachment predicted a faster RT to fear, which is in line with studies suggesting that one’s attachment style can modulate affective processing (Niedenthal et al, 2002) and that attachment anxiety could lead to a heightened state of vigilance to facial cues imbued with emotional meanings (Fraley et al, 2006). It is also well established that attachment is strongly affected by the quality of early carer–child interactions (Castro et al, 2015; McElwain, Halberstadt, & Volling, 2007; Salcuni, 2015), which can extend into adolescence (Canetti et al, 1997; Cooper et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Burgundy Johnson, DO, Nikki Mathur Grunewald, MS, PhD Candidate, Kelly Pelzel, PhD, Elizabeth Jarvis, MD M ary Ainsworth and John Bowlby described attachment as "a deep and enduring emotional bond that connects one person to another across time and space." 1 Evidence-based psychotherapies employing constructs from attachment theory have gained traction in early childhood mental health, though attachment is not often consciously considered when it comes to formulating clinical impressions during appointments. This is not to imply that providers are not meeting the attachment needs for families they serve, but rather that increased awareness of attachment processes offer insight into what makes relationships work and how to make the therapeutic alliance stronger.…”
Section: Utilizing Attachment Theory In Clinical Practicementioning
confidence: 99%